Gun barrel design optimisation using finite element analysis - Hameed, Amer (Cranfield University, 2000)
The strength of a gun barrel is a function of the residual circumferential stress at the bore. This stress is known to be affected by the properties of the gun barrel material, especially the Bauschinger effect. This thesis examines the influence of the constitutive relationship for various materials on the resultant stresses in the barrel. The work reported here consists of two major parts: experimental, and numerical analysis using the finite element method. The experimental work concerns the autofrettaging of selected test specimens and the gathering of data. Test specimens were heat-treated to give a range of strain hardening and initial yield stress characteristics. This was done in order to examine the influence of the Bauschinger effect on the resultant stress field for materials with various constitutive relationships. The numerical part of the work consists of the simulation of the tests using finite element methods. The results of the numerical simulation are compared with the experimental data. There is good agreement between the results, and they suggest that a. there is no significant effect on the reyield pressure of the test cylinders which have strain hardening; b. machining of the bore diameter increases the residual stress at the new bore diameter; c. machining of the outside diameter reduces the residual stress at the bore; d. most of the samples showed elastic relaxation due to the machining. However some localised plastic deformation was observed at the new surface in the case of machining at the inside diameter; e. machining does not cause the elastic-plastic interface to move; f. the influence of the Bauschinger effect increases with increase in tangent modulus (strain hardening); Further simulations were carried out to investigate the effect of boring gas evacuator holes or cross bores and results suggest that there is a severe localised loss of residual stress at the bore and the affected zone spreads to approximately 5 times the cross-bore diameter. The reyield pressure at the bore reduces by approximately 70%, suggesting that the benefit of autofrettaging is lost.